Conductive polymer composition and its uses

JP7631810B2Active Publication Date: 2025-02-19TOSOH CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021000581
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-05
Publication Date
2025-02-19
Estimated Expiration
2041-01-05

Smart Images

  • Figure 0007631810000001
    Figure 0007631810000001
  • Figure 0007631810000002
    Figure 0007631810000002
  • Figure 0007631810000003
    Figure 0007631810000003
Patent Text Reader

Abstract

To provide an electrolytic capacitor having good characteristics of low ESR while maintaining high capacity.SOLUTION: A conductive polymer composition comprises: 0.01 to 10 wt% of polythiophene (A) which can be produced by polymerizing a thiophene monomer represented by the following general formula (3) in water or an alcohol solvent in the presence of an oxidizing agent, followed by, if necessary, an acid treatment; 0.01 to 3 wt% of insulating inorganic particles (B) having a particle diameter (D50) of 80 nm or less; and water.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel conductive polymer composition and its use. [Background technology]

[0002] In recent years, conductive polymer materials have been developed by doping π-conjugated polymers, such as polyacetylene, polythiophene, polyaniline, and polypyrrole, with electron-accepting compounds as dopants, and their applications to, for example, antistatic agents, solid electrolytes for electrolytic capacitors, conductive paints, electrochromic elements, electrode materials, thermoelectric conversion materials, transparent conductive films, chemical sensors, actuators, etc., are being considered. In the field of electrolytic capacitors, there is a strong demand for electrolytic capacitors with high capacity and low ESR as electronic devices become faster and more frequent. Polythiophene-based conductive polymer materials are practically useful as conductive polymer materials that meet this demand because of their chemical stability.

[0003] Known examples of polythiophene-based conductive polymer materials include (i) a PEDOT / PSS aqueous dispersion solution obtained by polymerizing 3,4-ethylenedioxythiophene (EDOT) in an aqueous solution of polystyrene sulfonic acid (PSS) as a dopant, and (ii) so-called self-doped conductive polymers (e.g., sulfonated polyaniline, PEDOT-S, etc.) that have substituents (sulfo groups, sulfonate groups, etc.) that combine water solubility and doping properties directly or via a spacer in the polymer main chain (see, for example, Non-Patent Documents 1 and 2).

[0004] Electrolytic capacitors using PEDOT / PSS are known (Patent Document 1). However, since PEDOT / PSS exists in particulate form, it is known that it is difficult to fully utilize the capacity of an electrolytic capacitor because it cannot cover every corner of the surface of the electrolytic capacitor dielectric that has been subjected to expansion treatment. As a method for solving this problem, development is being carried out on self-doped conductive polymers that are water-soluble and have the potential to cover every corner of the surface of the electrolytic capacitor dielectric. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Journal of American Chemical Society,112,2801-2803(1990) [Non-Patent Document 2] Advanced Materials,Vol.23(38)4403-4408(2011) [Patent documents]

[0006] [Patent Document 1] JP 2017-147466 A Summary of the Invention [Problem to be solved by the invention]

[0007] A desirable characteristic of electrolytic capacitors is a low ESR. It is known that a low ESR electrolytic capacitor can be produced by filling the gaps between the electrodes of an electrolytic capacitor with a conductive polymer with high conductivity. Since PEDOT / PSS exists in a particulate form, it is easy to fill the gaps between the electrodes, making it easy to produce a low ESR electrolytic capacitor, but since self-doped conductive polymers are not particulate, it is difficult to fill the gaps between the electrodes, making it difficult to lower the ESR. There is a demand for improvement in the ESR characteristics of conventionally known self-doped conductive polymers.

[0008] Therefore, an object of the present invention is to provide a self-doped conductive polymer composition for producing an electrolytic capacitor having excellent properties such as low ESR while maintaining a high capacity. [Means for solving the problem]

[0009] As a result of intensive research aimed at solving the above problems, the present inventors have found that the conductive polymer composition described below can provide an electrolytic capacitor having excellent low ESR properties, and have thus completed the present invention.

[0010] That is, the present invention relates to a conductive polymer composition and a conductive polymer film as described below, and an electrolytic capacitor using the same. [1] A conductive polymer composition comprising 0.01 to 10% by weight of polythiophene (A) including at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.01 to 3% by weight of insulating inorganic particles (B) having a particle size (D50) of 80 nm or less, and water:

[0011] [ka]

[0012] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. [2] The conductive polymer composition according to [1], wherein the insulating inorganic particles (B) have a particle size (D50) of 60 nm or less. [3] The conductive polymer composition according to [1] or [2], wherein the insulating inorganic particles (B) are one or a mixture of two or more selected from the group consisting of aluminum oxide, titanium oxide, silicon dioxide, magnesium oxide, zinc oxide, barium titanate, strontium titanate, aluminum nitride, boron nitride, kaolin, hydroxyapatite, bentonite, and hydrotalcite. [4] The conductive polymer composition according to any one of [1] to [3], further comprising, in addition to the (A), (B), and water, a compound (C) selected from the group consisting of an alkali metal compound, ammonia, an organic amine compound, and a quaternary ammonium compound, and having a pH in the range of 1.5 to 10.0. [5] A conductive polymer film comprising: a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2); and insulating inorganic particles (B) having a particle size (D50) of 80 nm or less:

[0013] [ka]

[0014] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. [6] A method for producing a conductive polymer film according to [5], comprising applying and drying a conductive polymer composition containing 0.01 to 10% by weight of polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.01 to 3% by weight of insulating inorganic particles (B) having a particle size (D50) of 80 nm or less, and water:

[0015] [ka]

[0016] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. [7] An electrolytic capacitor comprising the conductive polymer film according to [5] above. Effect of the Invention

[0017] According to the present invention, it is possible to provide an electrolytic capacitor with a low ESR while maintaining a high capacitance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention will be described in detail below.

[0019] The present invention relates to a conductive polymer composition comprising 0.01 to 10% by weight of polythiophene (A) including at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.01 to 3% by weight of insulating inorganic particles (B) having a particle size (D50) of 80 nm or less, and water.

[0020] [ka]

[0021] [In the general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom.

[0022] The linear or branched alkyl group having 3 to 6 carbon atoms is not particularly limited, and examples thereof include an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, a 2-ethylbutyl group, and a cyclohexyl group.

[0023] The above R 2 From the viewpoint of film-forming properties, it is preferable that is a hydrogen atom, a methyl group, an ethyl group, or a fluorine atom, and more preferably is a hydrogen atom or a methyl group.

[0024] In the above general formulas (1) and (2), m represents an integer of 1 to 10, and from the viewpoint of film-forming properties, it is preferably an integer of 1 to 6, more preferably an integer of 1 to 4, and even more preferably 2 or 3.

[0025] In the above general formulas (1) and (2), n represents 0 or 1, and n is preferably 1 in terms of excellent electrical conductivity.

[0026] The structural unit represented by the above general formula (2) represents the doped state of the structural unit represented by the above general formula (1).

[0027] Dopants that cause an insulator-metal transition by doping can be divided into acceptors and donors. The former enters the vicinity of the polymer chain of a conductive polymer by doping and takes away π electrons from the conjugated system of the main chain. As a result, a positive charge (positive hole) is injected into the main chain, so it is also called a p-type dopant. Conversely, the latter donates an electron to the conjugated system of the main chain, and this electron moves through the conjugated system of the main chain, so it is also called an n-type dopant.

[0028] The dopant in the present invention is a sulfo group or a sulfonate group covalently bonded within the polymer molecule, and is a p-type dopant. A polymer that exhibits electrical conductivity without the addition of an external dopant is called a self-doped polymer.

[0029] The polythiophene (A) of the present invention can be produced by polymerizing a thiophene monomer represented by the following general formula (3) in water or an alcohol solvent in the presence of an oxidizing agent, and then optionally treating with an acid.

[0030] [ka]

[0031] In the above general formula (3), M represents a hydrogen ion or a metal ion. 2represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. The metal ion represented by M in the general formula (3) is not particularly limited, but examples thereof include transition metal ions, precious metal ions, non-ferrous metal ions, alkali metal ions (e.g., Li ions, Na ions, and K ions), and alkaline earth metal ions.

[0032] When the polymer obtained after polymerization of the thiophene monomer represented by the general formula (3) is a salt of a metal ion (when M is a metal ion), M can be converted to a hydrogen ion by treating the obtained metal salt polymer with an acid. That is, even if M in the general formula (3) is a metal ion, it is possible to produce a polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2). Furthermore, by mixing the polythiophene (A) with an alkali metal compound or an amine compound, it is possible to produce a polythiophene containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1') and the structural unit represented by the general formula (2').

[0033] The thiophene monomer represented by the above general formula (3) is not particularly limited, but specifically includes 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonic acid, sodium 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate, lithium 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate, ) hexane-1-sulfonic acid potassium, 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid, 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid sodium, 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid potassium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonic acid sodium, 3-[(2 ,3-Dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonic acid potassium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1- Sodium propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]- Sodium 1-fluoro-1-propanesulfonate, potassium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, ammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, Hydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate triethylammonium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate sodium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate potassium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate Examples include sodium 1-methyl-1-butanesulfonate, potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-butanesulfonate, sodium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonate, and potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonate.

[0034] In the present invention, the conductivity of the polythiophene (A) is not particularly limited, but it is preferable that the conductivity (electrical conductivity) in a film state is 10 S / cm or more.

[0035] The polythiophene (A) used in the present invention may be one synthesized based on publicly known information.

[0036] In the conductive polymer composition of the present invention, the concentration of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) is 0.01 to 10% by weight. From the viewpoint of excellent low ESR, the concentration of the polythiophene (A) in the conductive polymer composition of the present invention is preferably 0.05 to 8% by weight, more preferably 0.1 to 7% by weight.

[0037] The insulating inorganic particles (B) in the present invention having a particle diameter (D50) of 80 nm or less are not particularly limited, but examples thereof include any one or a mixture of any one selected from the group consisting of aluminum oxide, titanium oxide, silicon dioxide, magnesium oxide, zinc oxide, barium titanate, strontium titanate, aluminum nitride, boron nitride, kaolin, hydroxyapatite, bentonite, and hydrotalcite.

[0038] The insulating inorganic particles are characterized by having a particle diameter (D50) of 80 nm or less. From the viewpoint of excellent ESR characteristics and storage stability, the particle diameter (D50) is preferably 60 nm or less, and more preferably 50 nm or less.

[0039] The shape of the insulating inorganic particles (B) having a particle diameter (D50) of 80 nm or less is not particularly limited, and particles in the shape of fillers, rods, tubes, particles, etc. can be used.

[0040] In the conductive polymer composition of the present invention, the content of the insulating inorganic particles (B) having a particle diameter (D50) of 80 nm or less is characterized by being 0.01 to 3 weight %, but from the viewpoint of excellent low ESR, it is preferably 0.01 to 2 weight %, more preferably 0.1 to 2 weight %, and even more preferably 0.1 to 1 weight %.

[0041] The conductive polymer composition of the present invention may further contain a compound (C) capable of forming an ion pair with the sulfonic acid group of the polythiophene (A) in order to have an excellent low ESR. The compound (C) capable of forming an ion pair with the sulfonic acid group is not particularly limited, and examples thereof include alkali metal compounds, ammonia, organic amine compounds, and quaternary ammonium salts. These compounds react with the sulfonic acid group of the polythiophene (A) to form alkali metal ion salts, ammonium ion salts, organic ammonium ion salts, and quaternary ammonium ion salts of the polythiophene (A), respectively.

[0042] The alkali metal compound is not particularly limited, but examples thereof include alkali metal salt compounds (e.g., lithium chloride, potassium chloride, sodium chloride, rubidium chloride, cesium chloride, lithium bromide, potassium bromide, sodium bromide, rubidium bromide, cesium bromide, etc.) and alkali metal hydroxides (e.g., lithium hydroxide, potassium hydroxide, sodium hydroxide, rubidium hydroxide, cesium hydroxide, etc.).

[0043] The alkali metal ion salt of the lithiophene (A) can be prepared by adding the alkali metal compound to the conductive polymer composition of the present invention. The alkali metal ion is not particularly limited, but examples thereof include lithium ion, potassium ion, sodium ion, rubidium ion, and cesium ion.

[0044] The organic amine compound is not particularly limited, and examples thereof include primary, secondary, or tertiary organic amine compounds having a total carbon number of 1 to 30. More specific examples thereof include methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, normal-propylamine, isopropylamine, normal-butylamine, hexylamine, aminoethanol, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 1,4-butanediamine, triisobutylamine, triisopentylamine, triisooctylamine, imidazole, N-methylimidazole, 1,2-dimethylimidazole, pyridine, picoline, and lutidine.

[0045] By incorporating the organic amine compound in the conductive polymer composition of the present invention, the organic amine compound reacts with the polythiophene (A) to form an organic ammonium ion, and an organic ammonium ion salt of the polythiophene (A) is prepared. The organic ammonium ion is not particularly limited, but examples thereof include primary, secondary, and tertiary organic ammonium ions having a total carbon number of 1 to 30. More specifically, examples of the organic ammonium ion include methylammonium, dimethylammonium, trimethylammonium, ethylammonium, triethylammonium, normal-propylammonium, isopropylammonium, normal-butylammonium, hexylammonium, 2-hydroxyethylammonium, N,N-dimethyl-N-(2-hydroxyethyl)ammonium, N-methyl-N-(2-hydroxyethyl)ammonium, di(2-hydroxyethyl)ammonium, and the like. ammonium, N-methyl-N,N-di(2-hydroxyethyl)ammonium, N,N,N-tri(2-hydroxyethyl)ammonium, 2,3-dihydroxypropylammonium, N-methyl-N-(2,3-dihydroxypropyl)ammonium, N,N-dimethyl-N-(2,3-dihydroxypropyl)ammonium, 1,4-butanediammonium, triisobutylammonium, triisopentylammonium, triisooctylammonium, imidazole cation, N-methylimidazole cation, 1,2-dimethylimidazole cation, pyridinium ion, picolinium ion, or lutidinium ion.

[0046] The quaternary ammonium compound is not particularly limited, but examples thereof include tetramethylammonium chloride, tetraethylammonium chloride, tetra-n-propylammonium chloride, tetra-n-butylammonium chloride, and tetra-n-hexylammonium chloride.

[0047] By incorporating the quaternary ammonium compound in the conductive polymer composition of the present invention, the quaternary ammonium compound reacts with the polythiophene (A) to form a quaternary ammonium ion, thereby preparing a quaternary ammonium ion salt of the polythiophene (A). The quaternary ammonium ion is not particularly limited, but examples thereof include tetramethylammonium ion, tetraethylammonium ion, tetra-n-propylammonium ion, tetra-n-butylammonium ion, and tetra-n-hexylammonium ion.

[0048] In the conductive polymer composition of the present invention, the content of the above-mentioned compound (C) is preferably 0.001 to 20% by weight, and from the viewpoint of excellent low ESR, it is preferably 0.01 to 15% by weight, and more preferably 0.1 to 10% by weight.

[0049] In terms of excellent low ESR, the conductive polymer composition of the present invention preferably has a pH in the range of 1.5 to 10.0, more preferably in the range of 2.0 to 8.0, and even more preferably in the range of 2.5 to 7.0. The pH can be controlled by the type and content of the above-mentioned compound (C).

[0050] When the conductive polymer composition of the present invention contains the compound (C), a part or all of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) interacts with the compound (C) to form a polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1') and the structural unit represented by the general formula (2'). That is, a mixture of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) and the compound (C) and the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1') and the structural unit represented by the general formula (2') are the same.

[0051] [ka]

[0052] [In the above general formula (1') and general formula (2'), R 2 The definitions and preferred ranges of m and n are as shown in the above general formula (1) and general formula (2) R 2 The definitions and preferred ranges of n and m are the same as those of n. M represents a hydrogen ion, an alkali metal ion, an ammonium ion, an organic ammonium ion, or a quaternary ammonium ion. The alkali metal ion, ammonium ion, organic ammonium ion, and quaternary ammonium ion in M ​​are as described above.

[0053] The conductive polymer composition of the present invention may contain additives (D) other than those mentioned above.

[0054] The additive (D) other than the above is not particularly limited, but may be, for example, a binder, a surfactant, a solvent, etc. The additive (D) may be used alone or in combination of two or more.

[0055] The binder is not particularly limited, but is preferably, for example, a water-soluble resin, and more specific examples include polyvinyl alcohol, polyvinylpyrrolidone, cellulose, a water-soluble polyester resin compound, a water-soluble polyurethane resin compound, or a mixture of a polyhydric alcohol and an organic acid having two or more carboxyl groups.

[0056] Examples of the water-soluble polyester resin compound include polyethylene terephthalate, polytrimethylene terephthalate, etc. The water-soluble polyester resin compound may be a self-emulsifying type or a reinforced emulsifying type, but is preferably a self-emulsifying type water-soluble polyester resin compound from the viewpoint of water resistance and solvent resistance.

[0057] Examples of the water-soluble polyester resin compound include those that are readily commercially available, such as those manufactured by Toyobo Co., Ltd. under the trade name Vylonal, those manufactured by Takamatsu Oil Co., Ltd. under the trade name PES Resin, those manufactured by GOO Chemical Co., Ltd. under the trade name PLASCOAT, those manufactured by Toagosei Co., Ltd. under the trade name ARONMELT, those manufactured by Takamatsu Oil Co., Ltd. under the trade name PES Resin A, and those manufactured by DIC Corporation under the trade name Watersol.

[0058] The water-soluble polyester resin compounds may be used alone or in combination of two or more.

[0059] The water-soluble polyurethane resin compound is mainly used in industrial applications as a urethane resin emulsion, and may be a self-emulsifying type or a reinforced emulsion type, but is preferably a self-emulsifying water-soluble polyurethane resin compound from the viewpoint of water resistance and solvent resistance. The self-emulsifying type may be an anionic type, a cationic type, or a nonionic type, and any of them may be used. The water-soluble polyurethane resin compound is not particularly limited, but may be a polyether type, a polyester type, a polycarbonate type, or the like.

[0060] Examples of water-soluble polyurethane resin compounds that can be easily obtained commercially include those manufactured by Sanyo Chemical Industries, Ltd. under the trade names U-coat (registered trademark), Permalin (registered trademark), and Euprene (registered trademark), those manufactured by Kusumoto Chemical Industries, Ltd. under the trade name NeoRez, those manufactured by ADEKA Corporation under the trade name Adeka Bontitor (registered trademark), those manufactured by Meisei Chemical Industry Co., Ltd. under the trade name Pascol (registered trademark), and those manufactured by DIC Corporation under the trade name Hydran (registered trademark).

[0061] The water-soluble polyurethane resin compounds may be used alone or in combination of two or more.

[0062] The polyhydric alcohol is not particularly limited, but examples thereof include erythritol and pentaerythritol.

[0063] The organic acid having two or more carboxyl groups is not particularly limited, but examples thereof include adipic acid and phthalic acid.

[0064] The surfactant is not particularly limited, but for example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, fluorine-based surfactants, silicone-based surfactants, etc. can be used, and more preferably at least one selected from the group consisting of nonionic surfactants and amphoteric surfactants.

[0065] The anionic surfactant is not particularly limited, but examples thereof include sodium lauryl alcohol sulfate and sodium dodecylbenzenesulfonate.

[0066] The cationic surfactant is not particularly limited, and a commercially available product can be used, or a generally known product can be separately produced and used.

[0067] The nonionic surfactant is not particularly limited, but examples thereof include polyethylene glycol type surfactants, acetylene glycol type surfactants, polyhydric alcohol type surfactants, and polymer type nonionic surfactants.

[0068] The polyethylene glycol surfactant is not particularly limited, but examples thereof include ethylene oxide adducts of higher alcohols, ethylene oxide adducts of alkylphenols, ethylene oxide adducts of fatty acids, ethylene oxide adducts of polyhydric alcohol fatty acid esters, ethylene oxide adducts of higher alkylamines, ethylene oxide adducts of fats and oils, and ethylene oxide adducts of polypropylene glycols.

[0069] The acetylene glycol surfactant is not particularly limited, but examples thereof include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, Surfynol (manufactured by Air Products, registered trademark), and Olfine (manufactured by Nissin Chemical Industry Co., Ltd., registered trademark).

[0070] The polyhydric alcohol surfactant is not particularly limited, but examples thereof include fatty acid esters of glycerol, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol and sorbitan, fatty acid esters of sucrose, alkyl ethers of higher alcohols, and fatty acid amides of alkanolamines.

[0071] The amphoteric surfactant is not particularly limited, but examples thereof include betaine-type amphoteric surfactants, such as alkyl dimethyl betaine, lauryl dimethyl betaine, stearyl dimethyl betaine, and lauryl dihydroxyethyl betaine.

[0072] The fluorosurfactant is not particularly limited as long as it has a perfluoroalkyl group, and examples thereof include PLASCOAT (registered trademark) RY-2, perfluoroalkanes, perfluoroalkyl carboxylic acids, perfluoroalkyl sulfonic acids, and perfluoroalkyl ethylene oxide adducts.

[0073] The silicone surfactant is not particularly limited, but examples thereof include polyether-modified polydimethylsiloxane, polyetherester-modified polydimethylsiloxane, hydroxyl group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyester-modified polydimethylsiloxane, perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, and silicone-modified acrylic compounds.

[0074] In addition, fluorine-based surfactants and silicone-based surfactants are effective as leveling agents to improve the flatness of the coating film.

[0075] The solvent is not particularly limited, but may be, for example, alcohol, and more specific examples include methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, butoxyethanol, and ethylene glycol.

[0076] In the conductive polymer composition of the present invention, the content of the additive (D) is characterized by being 0.001 to 20% by weight, but from the viewpoint of excellent operability, it is preferably 0.01 to 15% by weight, and more preferably 0.1 to 10% by weight.

[0077] The conductive polymer composition of the present invention is characterized by containing 0.01 to 10% by weight of polythiophene (A) including at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), containing 0.01 to 0.5% by weight of a water-dispersible metal (B), and containing water.

[0078] The concentration (content) of the water is not particularly limited, but from the viewpoint of excellent workability, it is preferably in the range of 80 to 99.5% by weight, and more preferably 85 to 99.5% by weight.

[0079] The method for preparing the conductive polymer composition of the present invention is not particularly limited, but may be, for example, a method in which the aqueous solution or solid of the polythiophene (A), the insulating inorganic particles (B) having a particle diameter (D50) of 80 nm or less, and water as necessary are mixed and homogenized by stirring or the like. In this case, the compound (C), the additive (D), etc. may be added and mixed as necessary, or the conductive polymer composition containing the polythiophene (A) and the insulating inorganic particles (B) having a particle diameter (D50) of 80 nm or less may be prepared once, and then the compound (C), the additive (D), etc. may be added and mixed to adjust. Note that each material is preferably added to water and mixed, but the order in which the materials are added and mixed is not particularly limited, and the conductive polymer composition of the present invention can be prepared by mixing these materials in any order.

[0080] The temperature at which the mixture is mixed is not particularly limited, but may be, for example, from room temperature to heating, and is preferably 0° C. or higher and 100° C. or lower.

[0081] The atmosphere in which the mixture is mixed is not particularly limited, and may be air or an inert gas atmosphere.

[0082] In addition to the general mixing and dissolving operation using a stirrer tip or stirring blade, the mixture may be subjected to ultrasonic irradiation or homogenization (for example, using a mechanical homogenizer, ultrasonic homogenizer, high-pressure homogenizer, etc.) When homogenization is performed, it is preferable to perform the homogenization at a low temperature in order to prevent thermal deterioration of the polymer.

[0083] The concentration of each component in the conductive polymer composition of the present invention may be adjusted by the blending ratio, or may be adjusted by concentrating the mixture after blending. The concentrating method may be a method of distilling off the solvent under reduced pressure, or a method of using an ultrafiltration membrane.

[0084] In the conductive polymer composition of the present invention, the concentration of all components other than water is preferably in the range of 0.5 to 20% by weight, and more preferably in the range of 0.5 to 15% by weight.

[0085] Since the conductive polymer composition of the present invention is dried and dehydrated after application, a good uniform film can be obtained within the above concentration range.

[0086] The viscosity (20° C.) of the conductive polymer composition of the present invention is preferably 200 mPa·s or less, more preferably 100 mPa·s or less, and even more preferably 50 mPa·s or less.

[0087] The conductive polymer film of the present invention can be formed using the conductive polymer composition of the present invention. The method for forming the conductive polymer film of the present invention is not particularly limited, but may be, for example, a method in which the conductive polymer composition of the present invention is applied to or immersed in a substrate, and then dried.

[0088] The drying atmosphere may be any of air, inert gas, vacuum, and reduced pressure, but from the viewpoint of preventing deterioration of the polymer film, an inert gas atmosphere such as nitrogen or argon is preferred.

[0089] The substrate is not particularly limited, but examples thereof include glass, plastic, polyester, polyacrylate, polycarbonate, metal oxide, ceramics, and resist substrates.

[0090] The above-mentioned coating method is not particularly limited, but examples thereof include casting, dipping, bar coating, roll coating, gravure coating, flexographic printing, spray coating, spin coating, and inkjet printing.

[0091] The drying temperature for the coating film is not particularly limited as long as a uniform conductive film can be obtained, but is preferably in the range of room temperature to 300°C, more preferably in the range of room temperature to 250°C, and even more preferably in the range of room temperature to 200°C.

[0092] The thickness of the coating is not particularly limited, but is preferably 10 -2 ~10 2 The surface resistance of the resulting coating film is not particularly limited, but is preferably in the range of 1 to 10 9 Preferably in the range of Ω / .

[0093] The conductivity of the conductive polymer film obtained in the present invention is not particularly limited, but it is preferable that the conductivity (electrical conductivity) in the film state is 10 S / cm or more.

[0094] The conductive polymer film of the present invention can be used, for example, as an antistatic agent, a solid electrolyte for an electrolytic capacitor, a conductive paint, an electrochromic element, an electrode material, a thermoelectric conversion material, a transparent conductive film, a chemical sensor, an actuator, etc. In particular, it is extremely useful as a solid electrolyte for an electrolytic capacitor. When used in an electrolytic capacitor, it is possible to provide an electrolytic capacitor having excellent characteristics of low ESR while maintaining a high capacity.

[0095] The conductive polymer film is characterized by comprising a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the general formula (1') and a structural unit represented by the general formula (2'), and insulating inorganic particles (B) having a particle diameter (D50) of 80 nm or less. EXAMPLES

[0096] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited thereto.

[0097] The analytical instruments and measurement methods used in the examples are listed below.

[0098] [NMR measurement] Equipment: VARIAN, Gemini-200 [Method of producing conductive polymer film] Specifically, 0.5 mL of the composition of the present invention described below was applied to a 25 mm square alkali-free glass plate, heated on a hot plate in air at 60° C. for 30 minutes, and further heated at 200° C. for 60 minutes to obtain a conductive polymer film.

[0099] [Thickness measurement of conductive polymer film] Equipment: DEKTAK XT manufactured by BRUKER.

[0100] The conductive polymer film produced by the above production method was cut at intervals of 6.25 mm in the x direction and 6.25 mm in the y direction to expose the glass portion, and the film thickness at nine measurement points was measured in an atmosphere of 25°C and 50% RH.

[0101] [Measurement of surface resistivity of conductive polymer film] Apparatus: Mitsubishi Chemical Loresta GP MCP-T600. Using a surface resistance measuring instrument Loresta GP MCP-T600 and a measurement probe as an ASP, the surface resistance was measured at nine measurement points at intervals of 6.25 mm in the x direction and 6.25 mm in the y direction in an atmosphere of 25°C and 50% RH.

[0102] [Conductivity measurement of conductive polymer film] The electrical conductivity was calculated from the film thickness and surface resistivity of the conductive polymer film measured by the above-mentioned measuring method according to the following formula.

[0103] Conductivity [S / cm]=10 4 / (Surface resistivity [Ω / □]×film thickness [μm]) [Preparation of solid electrolytic capacitors] An aluminum foil having a thickness of 100 μm was used, and the surface of the aluminum foil was etched. An aluminum foil was welded to a part of the etched aluminum foil having a thickness of 100 μm, and an extraction wire was attached. The etched aluminum foil was immersed in an aqueous solution of ammonium dihydrogen phosphate having a concentration of 0.2 wt% at a liquid temperature of 80° C., and a direct current voltage of 130 V was applied for 20 minutes to form a dielectric layer of aluminum oxide (anode). Separately, an etched aluminum foil having a thickness of 50 μm and an extraction wire was used as a cathode, and a separator made of insulating paper was interposed between the anode and the cathode to prepare a wound element. Next, the wound element was immersed in a conductive polymer composition, taken out, and then dried at 150° C. for 30 minutes to obtain a solid electrolytic capacitor.

[0104] [Characteristics measurement of solid electrolytic capacitors] The characteristics of the solid electrolytic capacitors prepared by the above method were evaluated using the following equipment: initial capacitance [μF] at initial 120 Hz, ESR [mΩ] at initial 100 kHz, and leakage current [μA] after 2 minutes when 63 V was applied.

[0105] Equipment: Hioki E.E. Corporation LCR meter IM3536 Synthesis example 1. In accordance with Synthesis Examples 1 and 2 of the known literature (JP 2019-196443), an aqueous solution of poly(3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid [a polymer containing a structural unit represented by the following formula (4) and a structural unit represented by the formula (5)] (hereinafter referred to as "PEDOT-MPS") (conductive polymer aqueous solution) was prepared. The amount of polymer contained in the aqueous solution was 0.74 wt%. In addition, iron ions and sodium ions were contained at 44 ppm and 12 ppm (relative to the polymer), respectively. The conductivity of this polymer was 342 S / cm.

[0106] [ka]

[0107] Example 1 (Preparation of conductive polymer solution) The conductive polymer aqueous solution obtained in Synthesis Example 1 was dehydrated under reduced pressure to prepare an aqueous solution containing 2.0% by weight of PEDOT-MPS. 0.5 g of aluminum oxide (Sigma-Aldrich, product number 544833) having a particle size (D50) of less than 50 nm was added to 100 g of the aqueous solution containing 2.0% by weight of PEDOT-MPS, and the mixture was thoroughly stirred and mixed. Next, 0.4 g of ethanolamine was added and the mixture was thoroughly stirred and mixed to obtain a conductive polymer composition with a pH of 3. A solid electrolytic capacitor was produced using the conductive polymer composition according to the above-mentioned method, and the characteristics were evaluated. The evaluation results are shown in Table 1.

[0108] Example 2 The capacitor characteristics were evaluated in the same manner as in Example 1, except that 0.1 g of silicon dioxide (ADEKA Corporation, Adelite AT-20Q) having a particle diameter (D50) of 10 to 20 nm was used instead of 0.5 g of aluminum oxide having a particle diameter (D50) of less than 50 nm. Note that, in order to achieve pH=3, the amount of ethanolamine added was 0.4 g, as in Example 1. The evaluation results are shown in Table 1.

[0109] Comparative Example 1 A conductive polymer composition was prepared by the same procedure as in Example 1, except that 0.1 g of silicon dioxide (Sea Hoster KE-P10, manufactured by Nippon Shokubai Co., Ltd.) having a particle diameter (D50) of 100 nm was used instead of 0.5 g of aluminum oxide having a particle diameter (D50) of less than 50 nm in Example 1. However, a uniform dispersion was not obtained, and the capacitor characteristics could not be evaluated. In order to achieve a pH of 3, the amount of ethanolamine added was set to 0.4 g, as in Example 1. The evaluation results are shown in Table 1.

[0110] Example 3 The capacitor characteristics were evaluated in the same manner as in Example 1, except that 0.1 g of hydroxyapatite (Sigma-Aldrich, product number 900194) having a particle diameter (D50) of less than 50 nm was used instead of 0.5 g of aluminum oxide having a particle diameter (D50) of less than 50 nm in Example 1. In addition, the amount of ethanolamine added was 0.4 g, as in Example 1, to achieve pH=3. The evaluation results are shown in Table 1.

[0111] Example 4 The capacitor characteristics were evaluated in the same manner as in Example 1, except that 0.01 g of hydroxyapatite (Sigma-Aldrich, product number 900194) having a particle diameter (D50) of less than 50 nm was used instead of 0.5 g of aluminum oxide having a particle diameter (D50) of less than 50 nm in Example 1. In addition, the amount of ethanolamine added was 0.4 g, as in Example 1, to achieve pH=3. The evaluation results are shown in Table 1.

[0112] Example 5 The capacitor characteristics were evaluated in the same manner as in Example 1, except that 1 g of hydroxyapatite (Sigma-Aldrich, product number 900194) having a particle diameter (D50) of less than 50 nm was used instead of 0.5 g of aluminum oxide having a particle diameter (D50) of less than 50 nm in Example 1. In addition, the amount of ethanolamine added was 0.4 g, as in Example 1, to achieve pH=3. The evaluation results are shown in Table 1.

[0113] Comparative Example 2 The capacitor characteristics were evaluated in the same manner as in Example 1, except that 5 g of hydroxyapatite (Sigma-Aldrich, product number 900194) having a particle diameter (D50) of less than 50 nm was used instead of 0.5 g of aluminum oxide having a particle diameter (D50) of less than 50 nm in Example 1. In addition, in order to achieve pH=3, the amount of ethanolamine added was set to 0.4 g as in Example 1. The evaluation results are shown in Table 1.

[0114] Reference example 1 The conductive polymer aqueous solution obtained in Synthesis Example 1 was dehydrated under reduced pressure to prepare an aqueous solution containing 2.0% by weight of PEDOT-MPS. 0.4 g of ethanolamine was added to 100 g of the aqueous solution containing 2.0% by weight of PEDOT-MPS, and the mixture was thoroughly stirred to obtain an aqueous conductive polymer solution with a pH of 3. A solid electrolytic capacitor was produced using the aqueous conductive polymer solution according to the method described above, and its characteristics were evaluated. The evaluation results are shown in Table 1.

[0115] Reference example 2 0.3 g of ethanolamine was added to 100 g of a dispersion of poly(3,4-ethylenedioxythiophene) externally doped with polystyrene sulfonic acid (Clevios PH500 manufactured by Heraeus) and thoroughly stirred to obtain a conductive polymer dispersion with a pH of 3. A solid electrolytic capacitor was produced using the conductive polymer dispersion according to the method described above, and its characteristics were evaluated. The evaluation results are shown in Table 1.

[0116] Comparative Example 3 0.5 g of aluminum oxide with a particle size (D50) of less than 50 nm was added to 100 g of a dispersion of polystyrene sulfonic acid externally doped poly3,4-ethylenedioxythiophene (Clevios PH500 manufactured by Heraeus) and thoroughly mixed. Next, 0.3 g of ethanolamine was added and thoroughly mixed to obtain a conductive polymer dispersion with a pH of 3. A solid electrolytic capacitor was produced using the conductive polymer dispersion according to the above-mentioned method, and its characteristics were evaluated. The evaluation results are shown in Table 1.

[0117] Comparative Example 4 The capacitor characteristics were evaluated in the same manner as in Comparative Example 2, except that 0.1 g of silicon dioxide (ADEKA Corporation, Adelite AT-20Q) with a particle diameter (D50) of 10 to 20 nm was used instead of 0.5 g of aluminum oxide with a particle diameter (D50) of less than 50 nm. The amount of ethanolamine added was 0.3 g to achieve a pH of 3. The evaluation results are shown in Table 1.

[0118] [Table 1]

[0119] From the results shown in Table 1, Examples 1 to 5 using the conductive polymer composition of the present invention have the effect of achieving low ESR while maintaining high capacity. This is presumably the result of the conductive polymer composition of the present invention filling the gap between the anode foil and the cathode foil. Furthermore, it was found that when the conductive polymer composition of the present invention is used, an electrolytic capacitor with low leakage current can be obtained. This effect is presumably due to the conductive polymer composition of the present invention having a high ability to repair oxide film defects that occur in the process of manufacturing an electrolytic capacitor. When PEDOT / PSS was used instead, a decrease in capacity and an increase in ESR were confirmed. [Industrial Applicability]

[0120] As described above, by using the conductive polymer composition of the present invention, it is possible to provide an electrolytic capacitor having excellent characteristics such as low ESR while maintaining a high capacity.

Claims

1. A conductive polymer composition for producing an electrolytic capacitor (excluding compositions containing a fluorine-based surfactant), comprising 0.01 to 10% by weight of polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2): 【Chemistry 1】 [In general formulas (1) and (2), R2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.]

2. 2. The conductive polymer composition according to claim 1, wherein the insulating inorganic particles (B) have a particle size (D50) of 60 nm or less.

3. 3. The conductive polymer composition according to claim 1 or 2, wherein the insulating inorganic particles (B) are one or a mixture of two or more selected from the group consisting of aluminum oxide, titanium oxide, silicon dioxide, magnesium oxide, zinc oxide, barium titanate, strontium titanate, aluminum nitride, boron nitride, kaolin, hydroxyapatite, bentonite, and hydrotalcite.

4. The conductive polymer composition according to any one of claims 1 to 3, which further contains, in addition to (A), (B), and water, a compound (C) selected from the group consisting of an alkali metal compound, ammonia, an organic amine compound, and a quaternary ammonium compound, and has a pH in the range of 1.5 to 10.

0.

5. A conductive polymer film for electrolytic capacitors (excluding conductive polymer films containing a fluorine-based surfactant), comprising: polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2): 【Chemistry 2】 [In general formulas (1) and (2), R2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.]

6. 6. A method for producing a conductive polymer film according to claim 5, comprising applying and drying a conductive polymer composition containing 0.01 to 10% by weight of polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), 0.01 to 3% by weight of insulating inorganic particles (B) having a particle diameter (D50) of 80 nm or less, and water: 【Chemistry 3】 [In general formulas (1) and (2), R2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.]

7. An electrolytic capacitor comprising the conductive polymer film according to claim 5.

Citation Information

Patent Citations

  • Method for producing conductive resin cured product and composition for conductive resin cured product

    JP2005314671A

  • Carbon nanotube-containing composition, and composite formed from the same

    JP2008214587A

  • Heat-ray screening composition, resin laminated product, and method for manufacturing the resin laminated product

    JP2010116517A

  • Transparent conductive film

    JP2017112051A

  • Electrolytic capacitor manufacturing method and electrolytic capacitor

    JP2017147466A